The MDM2 Single-Nucleotide Polymorphism T309G Is Associated With the Development of Epimacular Membranes - Jiang, Heng; Yan, Bin; Meng, Zhishang; Zhang, Lusi; Lei, Hetian; Luo, Jing (Frontiers in Cell and Developmental Biology, 2022)
Purpose: To investigate the role of the mouse double minute 2 (MDM2) gene single-nucleotide polymorphism (SNP) T309G in the development of epimacular membranes (EMMs) by analyzing the genotype distribution and consistency of the polymorphism in paired membrane-blood samples. Methods: This was a cross–sectional genetic association study of patients with proliferative vitreoretinopathy (PVR) or EMMs. PVR membranes (PVRMs), internal limiting membranes (ILMs) (PVR-ILMs) and blood samples (PVR-blood) from patients with PVR, and EMMs, EMM-ILMs and EMM-blood from patients with EMMs were collected. The genotype of all samples was determined by Sanger sequencing. Sex composition, mean age, the genotype distribution of MDM2 T309G, the allelic frequency of the MDM2 SNP309 G allele (% G) and the somatic mutation rate at the MDM2 T309G locus (% M) were analyzed and compared. The PVR and healthy Chinese donor groups were used as controls for different comparisons. Results: The EMM group of 62 patients was older than the PVR group of 61 patients by an average of 8.87 years (p < 0.0001), but the two groups were statistically similar in the sex composition (p = 0.1754). Importantly, G allele carriers were at a higher risk of developing EMMs than non-G allele carriers (p = 0.0479; OR = 2.047). Moreover, EMM-blood exhibited a significantly higher % G than blood samples from healthy Chinese donors (EMM-blood: 56.78%, donors: 45.61%; p = 0.0256; OR = 1.567). Regarding membrane-blood consistency, % M was significantly different between PVRMs and EMMs (PVRMs: 2.63%, EMMs: 21.57%; p = 0.0097; OR = 10.18) but not between different types of ILMs (PVR-ILMs: 18.18%, EMM-ILMs: 29.17%; p = 0.6855). Furthermore, EMMs (p = 0.0053; OR = 8.250) and EMM-ILMs (p = 0.0233; OR = 14.40) from patients with preoperative macular holes were more predisposed toward somatic mutations at the MDM2 T309G locus than those from patients without preoperative macular holes. Conclusions:MDM2 T309G is associated with the development of EMMs. Herein, the MDM2 SNP309 G allele is first reported as an associated factor of EMMs in a Chinese population. In addition, EMMs and ILMs are genetically unstable at the MDM2 T309G locus, especially when complicated with preoperative macular holes.